Finding a Feasible Solution for a Simple LP Problem using Agents - Arie de Bruin; Tjark Vredeveld; Albert Wagelmans (Tinbergen Institute, 1999)
In this paper we will describe a Multi-Agent System which iscapable of finding a feasible solution of a specially structuredlinear programming problem. Emphasis is given to correctnessissues and termination detection.
Keywords: 330; Mathematische Optimierung; Theorie